Integration of EFQM excellence model and information systems criterion - Ismail, Rosli; Azmi Murad, Masrah Azrifah; A. Jabar, Marzanah; Nor, Rozi Nor Haizan; Mustapha, Norwati (Asian Research Publication Network, 2016)
Higher Education Institutions (HEIs) have become key institutions in the knowledge-based economy. Over the past decade, the Malaysian government has placed greater emphasis on improved efficiency and productivity in the HEI as an engine for promoting quality human capital for a knowledge-based economy. Importantly, the government raised the share of research and development in GDP from 1.5% in the Eighth Malaysia Plan (2000-2005) to 4.9% in the Ninth Malaysia Plan (2006-2010) for HEIs. As a result, there is a need to monitor the quality performance of HEIs to see if the governments objectives are being met. The European Foundation for Quality Management (EFQM) excellence model was introduced at the beginning of 1992 as the framework for assessing organizations for the European Quality Award. In fact, this model has been claimed to be the most widely used model of the national excellence awards in the European countries. However, it does not have Information Systems (IS) as a single criterion. The purpose of this paper is to evaluate the interrelationships between the EFQM excellence model and information systems criterion of Malcolm Baldrige National Quality Award (MBNQA) model in the HEIs of Malaysia. The paper identified ten (10) criteria from the research model: leadership; policy and strategy; people; partnership and resources; information systems; processes; people results; student results; society results and key performance results. We obtained 118 valid responses from person in charge of quality management in Malaysian HEIs. Structural equation model (SEM) is used to analyse the data and results indicate that the relationships among the research model followed the Information Systems-Quality Management theory and TQM theory.